A Conceptual Framework of Motivational Factors Influencing Continuous e-Wallet Usage in Malaysia Post-COVID-19 - Emma Abd Rahim; Jeffrey S.S Cheah (International Journal of Accounting and Finance in Asia Pasific (IJAFAP), 2025)
The global COVID-19 pandemic significantly boosted the adoption of digital payment methods, including e-wallets, but the factors influencing their continued use beyond the pandemic, particularly in Malaysia, remain insufficiently examined. This conceptual study proposes an integrated framework that combines the Technology Continuance Theory (TCT) with the Health Belief Model (HBM) to better understand Malaysians’ ongoing intention to use e-wallets post-pandemic. Through an extensive review of the literature, this framework explores critical factors such as confirmation, perceived ease of use, perceived usefulness, perceived susceptibility, perceived severity, satisfaction, and attitude, and their impact on sustained usage behavior. The model emphasizes the interplay of both technological features and health-related perceptions in shaping user decisions in a post-COVID environment. The insights derived offer practical implications for policymakers and e-wallet service providers aiming to improve user retention and advance cashless payment adoption. Additionally, this framework lays the groundwork for future empirical studies to test and expand knowledge of e-wallet continuance in Malaysia and comparable emerging markets. By explicitly integrating health belief constructs with technology adoption theories, this study contributes a fresh theoretical perspective to the digital payment literature